Principles of therapeutic contact: physician-patient - Ogłodek, Ewa; Moś, Danuta; Araszkiewicz, Aleksander (Polish Journal of Public Health, 2009)
The ability to communicate with patients is an important element of effective therapy. The quality of a relationship between physician and patient, the way of conveying information, the appropriate choice of words, the amount of time devoted to the patient as well as the nonverbal aspect of communication are all vital to recovery from illness. The high prevalence of chronic diseases, increasing social awareness and growing costs of treatment have created the need for new models of health care, proper of doctor-patient communication signifi cantly contributes to improved therapeutic outcomes and mutual satisfaction. The aim of the research is to discuss the importance of doctor-patient communication for the quality of life of patients. Information with patients receive should be focused and adjusted to both the particular patient population and the individual recipient. In order to ensure optimal treatment outcomes and patient satisfaction, health care professionals must be aware of the peculiarities of diseases, their nature and social stigma as well as the vital problems of the patient. Creation of an appropriate doctor-patient relationship begins with a transmission of information about the diagnosis, treatment and prognosis. The way this information is framed must take into consideration the high sensitivity of certain groups to verbal messages. Scientific research suggest that success of the treatment depends on how well informed both the doctor and the patient are. Inherent in creating the appropriate doctor-patient relationship is bioethics, which is an important element in the success of therapeutic intervention.